The characteristics of the lobular arrangement indicate the dynamic role played by the infrapatellar fat pad in knee kinematics. Issue 1 (4th April 2019) - Macchi, Veronica; Picardi, Edgardo Enrico Edoardo; Fontanella, Chiara Giulia; Porzionato, Andrea; Stecco, Carla; Tortorella, Cinzia; Favero, Marta; Natali, Arturo; De Caro, Raffaele
Abstract: The infrapatellar fat pad (IFP) is an intracapsular but extrasynovial structure, located between the patellar tendon, the femoral condyles and the tibial plateau. It consists of white adipose tissue, organised in lobules defined by thin connective septa. The aim of this study is the morphometric and ultrasonographic analysis of IFP in subjects without knee pathology during flexion‐extension movements. The morphometric study was conducted on 20 cadavers (15M, 5F, mean age 80.2 years). Ultrasound was performed on 24 volunteers with no history of knee diseases (5M, 19F, mean age: 45 years). The characteristics of the adipose lobules near the patellar tendon and in the deep portion of the IFP were evaluated. Numerical models were provided, according to the size of the lobules. At histological examination, the adipose lobules located near the patellar tendon were larger (mean area 12.2 mm 2 ± 5.3) than those at a deeper level (mean area 1.34 mm 2 ± 0.7, P < 0.001) and the thickness of the septa of the deepest adipose lobules (mean value 0.35 mm ± 0.32) was greater than that of the superficial one (mean value 0.29 mm ± 0.25, P < 0.001). At ultrasound, the IFP was seen to be composed of very large lobules in the superficial part (mean area 0.29 cm 2 ± 0.17 in extension), with a significant reduction in flexion (mean area 0.12 cm 2 ± 0.07, P < 0.01). The deep lobules were smaller (mean area 0.11 cm 2 ± 0.08 in extension) and did not change their values (mean area 0.19 cm 2 ± 0.52 in flexion, P > 0.05). In the sagittal plane, the reduction of thickness of the superficial layer (with large adipose lobules) during flexion was 20.6%, whereas that of the deep layer (with small adipose lobules) was 1.3%. Numerical simulation of vertical loads, corresponding to flexion of the knee, showed that stress mainly developed within the interlobular septa and opposed bulging of the lobules. The characteristics of the lobular arrangement of the IFP (large lobules with superficial septa in the superficial part and small lobules with thick septa in the deep one), significant changes in the areas and perimeters of the superficial lobules, and the reduced thickness of the superficial layer during flexion all indicate the dynamic role played by the IFP in knee kinematics.